Study of Growth and Production of Tomato Cultivars In Response to Fruit Thinning at Tamansari, Tasikmalaya, West Java, Indonesia - Yunita, Roza; Isnaeni, Selvy (Department of Agronomy and Horticulture, IPB University, 2020)
Tomato is a horticultural crop that is widely cultivated in Indonesia because of its multipurpose uses. The prospect of marketing tomatoes is quite promising for local, national and export markets. The demand of tomato consumption has been increasing, but has not been supported by the availability of quality and quantity production. The area for tomato production has even been decreasing, especially in West Java, Indonesia. One of the causes of the low tomato production in Indonesia is due to the unavailability of superior varieties at the farm level, and very limited information on suitable farming technology. In addition, farmers have difficulty meeting supermarket and export standards because of the mismatch of the quality required by the market and the quality of the products. Efforts that can be made to improve the quality of tomato fruits includes the use superior varieties, and to apply better management of crop production. This study aims to determine the tomato variety which is suitable and high yielding to grow in Tamansari sub-district, Tasikmalaya, West Java, Indonesia, and to understand the effects of thinning fruit on tomato production. The study was carried out from August to November 2018 in Taman Sari, Tasikmalaya City, in a completely randomized design with tomato variety and fruit thinning as the treatments. The study used three tomato cultivars, “Betavila”, “Tymoti”, “Martha”. The levels of fruit thinning tested were 15%, 25%, and without fruit thinning as control. The results demonstrated that the choice of tomato variety and fruit thinning had very significant effects on the yield component of tomato. “Marta” is one of the suitable varieties suggested to be cultivated in the area in Tasikmalaya, and fruit thinning at 25% gave the highest fruit yield.